Analysis and optimal control of smart damping for porous functionally graded magneto-electro-elastic plate using smoothed FEM and metaheuristic algorithm. (15th May 2022) - Nguyen-Thoi, T.; Ly, Khuong-Duy; Truong, Tam T.; Nguyen, Sy-Ngoc; Mahesh, Vinyas
Abstract: This paper proposed an effective numerical approach for free vibration analysis and optimal control of the porous functionally graded magneto-electro-elastic (PFGMEE) plates integrated with the active constrained layer damping (ACLD). Specifically, in order to analyze the free vibration characteristic of the PFGMEE plates based on the layer-wise shear deformation theory, a cell-based smoothed discrete shear gap (CS-DSG3) method is applied. The accuracy and convergence of the CS-DSG3 method are demonstrated by comparing its results with those available in the literature. Additionally, due to the coupling characteristic between magnetic, electric, and elastic fields, the coupled response of the PFGMEE plate is also considered. Furthermore, in order to obtain the optimal performance of the PFGMEE plates with the ACLD treatment, a combination of the CS-DSG3 method with an adaptive elitist differential evolution (aeDE) algorithm is used to determine the optimal placement of ACLD patches and the piezoelectric fiber orientation angle of the PFGMEE plates. The effect of several boundary conditions and porous distribution types on the free vibration response and the optimal control solution of the PFGMEE plates is also examined. Highlights: An effective numerical approach for optimal control of PFGMEE/ACLD plates is proposed. A CS-DSG3 method is applied based on the layer-wise shear deformation theory. An aeDE algorithm is employed as an optimizer for optimal control. The approach reduces the computational cost while still achieves accurate optimal results.